Analysis of existing effectiveness and method to enhance the lightning, shielding and earthing protection schemes applied on the Parit Raja’s Telecommunication Tower System - Mohd Kasim, Ct Valkyis (2013)
Lightning, one of nature’s most destructive forces, continues to wreck havoc on lives and property especially in today’s electronic environment. It has been shown by field experiences that telecommunication towers are one of the preferential points for direct lightning strike. This is mainly connected with the specific features of their construction where the presence of high telecommunication towers and their topographical location mostly at an open area or at hills. The potential of lightning strike toward communication tower is high. A telecommunication tower located at Parit Raja town was chosen as a case study. The location of the tower is good to channel the coverage toward the community. Unfortunately this tower is very vulnerable to lightning strike and can giving impact to the surrounding buildings located nearby the tower itself such as mosque, petrol pump, post office and the Bank Simpanan National (BSN) bank. This thesis presents work that look at the current protection scheme against the lightning strike and the effect on a telecommunication tower system and the surrounding. Analysis study had been made towards existing protection component or system and their effectiveness in mitigating the lightning strike impact on the Parit Raja tower system. The investigation of the lightning protection system used by the communication tower is sufficient enough to direct the overload voltages of a lightning strike. Also, the analysis on the existing grounding earthing system is able to accommodate and dissipate the surge current to the earth. The method such as rolling sphere and cone protection had been used to identify the safety area on the site due to direct strike. Some suggestions to enhance the tower system protection such as installation external ground bus bar, radial system, and new installation for connection of coaxial cable and underground cable. Overall from this project, the weaknesses of system protection were identified in the tower Parit Raja and the proposal as improvement for the protection scheme in the future.